2020
DOI: 10.1371/journal.pone.0229914
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from rat-bone-marrow mesenchymal stromal/stem cells improve tendon repair in rat Achilles tendon injury model in dose-dependent manner: A pilot study

Abstract: Mesenchymal stromal/stem cells (MSCs) are increasingly employed for tissue regeneration, largely mediated through paracrine actions. Currently, extracellular vesicles (EVs) released by MSCs are major mediators of these paracrine effects. We evaluated whether rat-bonemarrow-MSC-derived EVs (rBMSCs-EVs) can ameliorate tendon injury in an in vivo rat model. Pro-collagen1A2 and MMP14 protein are expressed in rBMSC-EVs, and are important factors for extracellular-matrix tendon-remodeling. In addition, we found pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(100 citation statements)
references
References 31 publications
2
90
0
Order By: Relevance
“…The role of EVs as vehicle of TERT protein was addressed by Radeghieri et al, who tested primary amniotic fluid cells isolated from 25 subjects and found TERT in ∼30% of exosome samples (8 out of 25) (Radeghieri et al, 2017). More recently, the group detected TERT protein in rat bone marrow-MSC-derived EVs (Gissi et al, 2020). An interesting finding from Wang et al associated telomeric repeat-containing RNA (TERRA) fragments to EVs.…”
Section:  Tertmentioning
confidence: 99%
“…The role of EVs as vehicle of TERT protein was addressed by Radeghieri et al, who tested primary amniotic fluid cells isolated from 25 subjects and found TERT in ∼30% of exosome samples (8 out of 25) (Radeghieri et al, 2017). More recently, the group detected TERT protein in rat bone marrow-MSC-derived EVs (Gissi et al, 2020). An interesting finding from Wang et al associated telomeric repeat-containing RNA (TERRA) fragments to EVs.…”
Section:  Tertmentioning
confidence: 99%
“…As ideal effector molecule carriers and biocompatible therapeutic tools with pure biogenic derivation, EVs are becoming rising stars in treating illness, showing pleiotropic function and prompting encouraging results in various organs and systems [28][29][30]. Tendon repair has already been found to be promoted by EVs from BMSCs and ADSCs [9,10,31]. Motivated by the powerful repair and mass production capabilities of HUMSCs, HUMSC EVs have also been widely studied and applied in regenerative medicine [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have witnessed the emergence of extracellular vesicles (EVs) as a desirable therapeutic modality. Satisfactory results were obtained for inflammation resolution and tendon healing by EVs derived from bone marrow mesenchymal stem cells (BMSCs), which showed good prospects for EVs application after tendon injury [9,10]. These natural nanosized (30-150 nm in diameter) membrane-bound particles have the advantages of high biosafety and good in vivo stability and are thus superior vehicles for effector molecule delivery [11].…”
Section: Backgroudmentioning
confidence: 99%
“…We also tested the effects of a higher dose, by increasing the number of vesicles by a factor of 3, but both doses provided comparable results. Other groups have also used cell-equivalent doses [ 52 , 53 ] or doses which are in the same order of magnitude as ours [ 54 , 55 ], while others have successfully used even higher doses in animal models [ 51 ]. One of the studies that used cell-equivalent doses observed greater therapeutic effects using MSCs than MSC-derived EVs alone in vivo [ 53 ].…”
Section: Discussionmentioning
confidence: 99%